PLASMID CURING OF LOCAL ISOLATES OF KLEBSIELLAPNEUMONIAE ISOLATED FROM URINARY TRACTINFECTIONS AND ITS ROLE IN MULTIDRUG RESISTANCE - Faraj, Dimah; Ghanima, Kais (Iraqi Journal of Science, 2024)
Curing of plasmid for 7 local isolates of K. pneumoniae have multi-drug resistanceand isolated from urinary tract infections (UTI) by using acridin orange and sodiumdodecyl sulphate (SDS) were investigated.These results showed that the local isolates of K. pneumoniae were very resist(100%) to Ampicillin, Pepracillin, Amoxicillin, Penicillin G, Tetracyclin,Erythromycin and Gentamycin, high resist (71–80%) to Cephalexin, Cephalothin,Ceftazidine, Ciprofloxacin, Streptomycin and Tobramycin, moderate resist(43–57%) to Cefaclor, Cephradin and Naldixic acid and weak resist (29%) toCefotaxime while they were susceptible to Chloramphenicol and Amikacin.t was found that SDS is more efficient in curing than Acridin orange, hence thelosing of the resistance of antibiotics by using SDS was in the range (70–100%)while by using Acridin orange was in the range (28– 100%). After curing of plasmidthe Antibiotics resistance losed for Pipracillin, Amoxicillin, Penicillin G,Cephalexin, Cephalothin, Ceftazidin, Tetracyclin, Gentamycin and Tobramycin, thisresult confirm that the resistance of these antibiotics is born on plasmid, while theresistance of Ampicillin, Ciprofloxacin, Erythromycin and Streptomycin not losed,this result confirm that there resistance genes are born on the chromosome.